The Europeanization of Industrial Relations in Ireland and Italy - (:unkn) unknown (My University, 2012)
How is European integration affecting patterns of capital-labour interaction? More specifically, how is the inclusion of interest associations at the European level affecting the behavior of domestic interest associations? This dissertation contributes to the perennial debate over models of capitalism, focusing on the core component of industrial relations in Western Europe. In particular, the dissertation attempts to answer three questions: (1) how the European Trade Union Confederation (ETUC) and BusinessEurope as new political actors have influenced domestic interest configurations; (2) how negotiation at the supranational level affects the strategies of central actors in domestic industrial relations systems; and (3) if and how pressure from the European integration project modifies the institutional legacies of domestic IR systems. Using Ireland and Italy as case studies, this dissertation examines the impact of two external factors on each country's industrial relations system: interest aggregation and representation at the EU level, and the 2002 EU Directive on the Information and Consultation of Employees. The findings suggest that the development of the EU and related supranational interest confederations generate pressure over time on domestic industrial relations systems to decentralize collective bargaining to the company level. European integration has shaped the development of a new model of capitalism - one which ties market responsiveness to meso-level corporatism - while also addressing the more perennial questions of institutional endurance, path-dependence, and change.
Keywords: Industrial relations--European Union countries--Case studies; Industrial relations--Ireland; Industrial relations--Italy; European Union countries--Economic integration; Industrial relations--International cooperation